The quintessentially democratic act? Democracy, political community and citizenship in and after the UK's EU referendum of June 2016. Issue 5 (29th July 2017) - Shaw, Jo
Abstract: On 23 June 2016, the United Kingdom voted to leave the European Union, by a rather small majority. Although much about the future relations between the EU and the UK remains uncertain, it is already possible to explore in more detail the issues of democracy, political community and citizenship which were thrown up by this referendum result. The article explores the reconstruction of the vote as the 'will of the people', in the light of the principle of demoi-cracy which suggests a more nuanced approach to the issue of democratic consent in complex multi-level polities such as the UK and the EU. Specific questions are raised about the narrowness of the referendum franchise, and about the consequences that flow from the territorially differentiated result of the referendum, with Scotland in particular voting strongly 'to remain'.